Maintenance and management issues in commercial building - Mohamad, Mohamad Fildza Azwan; Md Radzi, Mohammad Fitrie; Mohd Parid, Mohamad Firdaus; Mohd Nawi, Mohd Nasrun (2013)
This study will discuss the problems and issues that appear in the building management in commercial building in Malaysia.The research was conducted by collecting data from journal articles about the building management issue.Good management of the building will be able to influence the quality of the buildings that remain long, safe and beautiful without any damage and problems.In addition, building a good management can ensure that the facilities available in the building are well and meet the standard.Thus, exposure to the problems and needs in the management of the building would be able to help improve building management systems to be more effective.